Implementing a progressive resistance training program in youth junior Olympic women's gymnastics - Lockard, M. M.; Gable, T. F. (Science of Gymnastics Journal, 2022)
Competitive gymnasts in the Women`s Junior Olympic (JO) program are highly conditioned, typically training 8-20 hours per week. Training often consists of high-repetition body-weight activities with little variability. This method of training lacks progressive resistance exercise (PRE) training, a cornerstone for muscular adaptation. To investigate the benefits of 10 weeks of PRE training, 1 day/week, on muscular strength and power in women`s JO child and adolescent gymnasts. 50 females aged 7-17 years (mean 10.2±2.7 years), competing on JO levels 3-10 participated. Gymnasts in JO Levels 3 and 4 were divided into either the Control Group or the PRE group. The Control Group continued the standard non-PRE conditioning. The PRE Group underwent the prescribed PRE training. Level 5-10 gymnasts also underwent PRE training and were separately analyzed in a quasi-experimental repeated measures design. 15 exercises were completed. Tests for lower- and upper-body power included vertical leap and a modified Wingate arm-ergometer anaerobic test (Arm-WAnT). Compared to the Control Group, the PRE Group had a greater improvement in vertical power (p=0.003), and Arm-WAnT peak power and mean power (p=0.044 and 0.023), but no difference in Arm-WAnT fatigue index. Gymnasts in Levels 5 to 10 similarly improved vertical power (2224±756W to 2473±688W, p<0.001), Arm-WAnT peak power (80.9±30.1W to 93.2±40.6W, p<0.001), and mean power (62.8±23.2 to 70.1±27.3, p<0.001), with no change in Arm-WAnT fatigue index. 10 weeks of PRE will improve upper- and lower-body power in child and adolescent female JO gymnasts.